RIPK2-Mediated Autophagy and Negatively Regulated ROS-NLRP3 Inflammasome Signaling in GMCs Stimulated with High Glucose - Chenlin Gao; Jiao Chen; Fang Fan; Yang Long; Shi Tang; Chunxia Jiang; Jiying Wang; Youhua Xu; Yong Xu (Mediators of Inflammation)
Background. Hyperglycemia plays a vital role in diabetic nephropathy (DN); autophagy and its potential upregulator receptor-interacting protein kinase 2 (RIPK2) are associated with ROS, which play a potential role in regulating NLRP3, and may be involved in inflammation in DN. Aim. In this study, we aimed to explore the mechanisms mediated by RIPK2 in autophagy and the relationship with ROS-NLRP3 of DN, by investigating the levels of RIPK2 and autophagy in glomerular mesangial cells (GMCs) stimulated with high glucose. Material and Methods. GMCs were divided into the following groups: normal group (NC), high glucose group (HG), and RIPK2 siRNA group. RIPK2, LC3, caspase1, and IL-1β levels were measured by western blotting and RT-PCR. Autophagosomes were measured by GFP-RFP-LC3; ROS were detected by DCFH-DA. Results. High glucose upregulated RIPK2 and LC3 in GMCs during short periods (0-12 h) (p<0.01), while RIPK2 and LC3 were significantly downregulated in the long term (12-72 h) (p<0.01); these changes were positively correlated with glucose concentration (p<0.01). In addition, levels of ROS, caspase1, and IL-1β increased in a time- and dose-dependent manner in the high glucose group, even with an increased expression of LC3 (p<0.01). However, LC3 expression decreased in the siRIPK2 group, while levels of ROS, caspase1, and IL-1β increased (p<0.01). Conclusions. Autophagy was activated by high glucose at short time periods but was inhibited in the long term, demonstrating a dual role for high glucose in autophagy of GMCs. RIPK2 regulates ROS-NLRP3 inflammasome signaling through autophagy and may be involved in the pathogenesis of DN.